Differential effects of Rho-kinase inhibitor and angiotensin II type-1 receptor antagonist on the vascular function in hypertensive rats induced by chronic l-NAME treatment - Bainian Chen (Acta Pharmaceutica Sinica B, 2012)
Little attention has been paid to the effect of Rho-kinase inhibitor on the vascular dysfunction of nitric oxide-deficient hypertension. We aimed to investigate whether the Rho-kinase inhibitor fasudil showed beneficial effect on the vascular dysfunction of the NG-nitro-l-arginine methyl ester (l-NAME) treated rat, as well as to compare the differential effects of fasudil and angiotensin II receptor antagonist valsartan on vascular function. In the present study, both valsartan and fasudil exerted antihypertensive action on the l-NAME-treated rats, while only valsartan attenuated the cardiac hypertrophy. Treatment with valsartan showed improvement on vascular reactivity to norepinephrine, KCl and CaCl2, whereas fasudil therapy showed little effect on vasoconstriction. Endothelium-dependent vasodilation to acetylcholine was reduced in the NO-deficient group but was normalized by the fasudil therapy. The increased expression of RhoA and Rho-kinase (ROCK) in the vasculature was corrected well to normal level by either valsartan or fasudil administration, which seemed to be at least partially responsible for the beneficial effect of the drug infusion. These findings suggest that the angiotensin II receptor antagonist interferes more with the contractile response than Rho-kinase inhibitor, whereas inhibition of Rho-kinase activity exhibits a better improvement on vasorelaxation than blockade of angiotensin II receptor.